A prospective study on the association between post-voiding residual volume and quality of life during bacille Calmette-Guérin (BCG) instillation therapy for non–muscle-invasive bladder cancer. (July 2021) - Kikuchi, Daichi; Kato, Yoichiro; Takayama, Misato; Kanzaki, Seiko; Ito, Akito; Ikarashi, Daiki; Maekawa, Shigekatsu; Kato, Renpei; Seo, Takashi; Owari, Yukihisa; Nozawa, Tatsuru; Isurugi, Kazumasa; et al.
Objectives: The aim of this study was to investigate the relationship between quality of life (QOL) and residual urine volume in patients undergoing bacille Calmette-Guérin (BCG) therapy. Methods: Patients requiring BCG therapy, including those with carcinoma in situ, were enrolled prospectively. The urine volume collected through urethral catheterization was measured as post-voiding residual volume (PVR) during BCG therapy. Patients were divided into two groups: small PVR (SPVR), with PVR less than 30 ml, and large PVR (LPVR), with PVR greater than or equal to 30 ml. QOL status was assessed using the European Organisation for Research and Treatment of Cancer (EORTC) QLQ-C30 system before and after BCG therapy. Moreover, some patients were assessed by International Prostate Symptom Score (IPSS) at the same time as assessment with the EORTC QLQ-C30 system. The primary end point was the evaluation of QOL during BCG therapy. Results: Among the 69 patients with non–muscle-invasive bladder cancer included in this study, 43 were in the SPVR group and 26 were in the LPVR group. The proportions of women and analgesic use in the SPVR group were higher than that in the LPVR group; however, medication use for dysuria in the SPVR group was less than that in the LPVR group. In the QOL analyses, cognitive function and emotional function in the functional scale and fatigue, nausea/vomiting, and dyspnoea in the symptomatic scale were worse in the SPVR group than in the LPVR group. In the multivariate analysis, fatigue was worse in the SPVR group than in the LPVR group. Conclusions: During BCG therapy, patients in the SPVR group had worse QOL, especially fatigue, than those in the LPVR group. Level of evidence: Not applicable for this multicentre audit.